A Two‐Tailed Phosphopeptide Crystallizes to Form a Lamellar Structure. Issue 12 (13th February 2017) - Pellach, Michal; Mondal, Sudipta; Harlos, Karl; Mance, Deni; Baldus, Marc; Gazit, Ehud; Shimon, Linda J. W.
Abstract: The crystal structure of a designed phospholipid‐inspired amphiphilic phosphopeptide at 0.8 Å resolution is presented. The phosphorylated β‐hairpin peptide crystallizes to form a lamellar structure that is stabilized by intra‐ and intermolecular hydrogen bonding, including an extended β‐sheet structure, as well as aromatic interactions. This first reported crystal structure of a two‐tailed peptidic bilayer reveals similarities in thickness to a typical phospholipid bilayer. However, water molecules interact with the phosphopeptide in the hydrophilic region of the lattice. Additionally, solid‐state NMR was used to demonstrate correlation between the crystal structure and supramolecular nanostructures. The phosphopeptide was shown to self‐assemble into semi‐elliptical nanosheets, and solid‐state NMR provides insight into the self‐assembly mechanisms. This work brings a new dimension to the structural study of biomimetic amphiphilic peptides with determination of molecular organization at the atomic level. Abstract : A designed β‐hairpin phospholipid‐inspired phosphopeptide crystallizes to form a lamellar structure that is stabilized by a variety of hydrogen‐bonding interactions. The crystal structure together with ssNMR provide insight into the molecular arrangement within the self‐assembled semi‐elliptical nanosheets. The crystal structure could prove valuable for enhancing the predictability of intermolecular interactions for the design of self‐assembling oligopeptides.